REAKSI PASAR TERHADAP PENGUMUMAN MERGER PERUSAHAAN-PERUSAHAAN DI INDONESIA - admin, GERRI ANDRA DJ B11112062 (Jurnal Manajemen Update, 2016)
The aim of this research is to analyze the reaction of merger information toward the abnormal return and trading volume in the companies listed in Indonesian Stock Exchange (IDX). The research samples are the companies that have done the merger in the period between 2011 and 2015. Using purposive sampling, there are 43 companies that fulfill the criteria. Event study method is selected for this research and paired sample t-test is used to test the hypotesis. The result of the paired sample t-test shows that there are differencesÂ  between the abnormal return (in average) of stocks before and after the merger. The researcher found that the abnormal return (in average) of stocks before merger is -0.01536470 compared to 0.03281980 after merger. It means that the market is not efficient yet. While, there is significantly difference in stock trading volume in the period of merger, which has average stock trading volume 0.00268700 before merger and average stock trading volume 0.00305380 after merger. Keyword : Merger, Abnormal Return, Trading Volume activity